1956
DOI: 10.1099/00221287-14-2-290
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Studies of the Virus System of Vesicular Stomatitis

Abstract: SUMMARY : Biophysical studies of the virus system of vesicular stomatitis passaged in eggs showed that the major part ofthe infectivity was associated with a component of sedimentation coefficient 625 S. A component of sedimentation coefficient 330 S was observed also, and is probably a non-infective product of the disintegration of the 6 2 5 s component. These components contribute about 35 yo of the total complement-fixing activity of the virus system. All infective materials were handled in subdued light (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 11 publications
6
18
0
Order By: Relevance
“…The 15 mp strand may arise as a filamentous extrusion from the 3rd and 4th structural layers (Fig. 2) and is consistent with the slowly sedimenting (Bradish et al 1956) and rapidly diffusing (Warrington, 1965) infective component.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The 15 mp strand may arise as a filamentous extrusion from the 3rd and 4th structural layers (Fig. 2) and is consistent with the slowly sedimenting (Bradish et al 1956) and rapidly diffusing (Warrington, 1965) infective component.…”
Section: Discussionsupporting
confidence: 55%
“…and then to rest in the L40 tubes. Sampling operations in subdued light and recoveries of infectivity were generally as described by Bradish, Brooksby & Dillon (1956).…”
Section: -2mentioning
confidence: 99%
“…makes it difficult to correlate the observed different forms (rods and spherical particles) with a sequence of developing structures. One can speculate, however, about the development of the virus rods from the spherical particles for the following reasons: (a) the 60-to 65-m# particles (which possibly represent the noninfectious complement-fixing particles described by Bradish et al (2)) and the virus rods were visible inside the same vacuole (Fig. 7) ; and (b) the diameter of 60 to 65 m/z was also found for the core of the 90-to 100-m/z particles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their dimensions have been reported to be 210 )< 60 (1) or 175 )< 69 mg (2). Furthermore, Bradish et al (2) found non-infectious spherical particles, 65 mg in diameter, possessing a virusspecific complement-fixing activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation